About Pigmented Nanoflagellates and the Importance of Mixotrophy in a Coastal Upwelling System - Figueiras, Francisco G.; Arbones, Belén; Castro, Carmen G.; Froján, María; Teixeira, Isabel G. (Frontiers in Marine Science, 2020)
Mixotrophy, understood as food ingestion and photosynthesis occurring in the same organism, is a nutrition mode relatively common in marine protists. Among these, pigmented nanoflagellates 2-20 µm in size (PNF) are now known to be responsible for a significant part of consumption of bacteria in the open ocean. However, knowledge about the importance of the mixotrophic nutrition of these organisms in coastal upwelling systems, where autotrophy prevails, is very limited. Here we compile the limited available information about mixotrophy of PNF in coastal upwelling systems, focusing on the NW Iberian upwelling, to show that this type of nutrition is relevant in these productive systems and to urge for further studies. Several indirect approaches allow inferring that mixotrophy was significant for PNF in the NW Iberian upwelling, with heterotrophy supplying seventy-five percent of the total carbon requirements in this plankton group. This new insight has major implications for our view of marine food webs in coastal upwelling regions, and must be taken into account in the construction of more accurate biogeochemical models of the transfer of matter and energy in these marine areas.